Strategi Kepala Madrasah dalam Meningkatkan Karakter Peserta Didik di Ma Al-Anwar Bunder Pancoran Bondowoso - Khoir, Qoidul; Rofiq, Ainur (Faidatuna, 2023)
Islamic education as a sub system of national education who has a purpose to form the character of student be a human being who believes, devoted to god almighty and have a noble character, as a provision for printing student who have a quality personality, that is to have a balance of morals and knowladge. The are so many poor education carry out and ignore its importance character building in students especially in elementary school age, therefore it is necessary to instill character through the activities of the dhuha prayer habituation, and istighosah for better personal printing. The purpose of this research is to describe implementation of the strategy of the principal by building teacher collaboration, as well as the result of character enhancement in improving the character of student islamic Al-Anwar Bunder Pancoran Bondowoso. The research method used is with a qualitative approach that result narrative data in the form of natural explanations. Methods of data collection using observation, interview, and documentation. While the method of analysis uses an interactive model analysis method. Meanwhile the presentation of the data by drawing a conclusion, and to get the validity of the data using data validity with triangulation techniques. Based on research results, then it can be found that strategy of the madrasa principal in improving the character of student islamic Al-Anwar Bunder Pancoran Bondowoso school namely through teacher cooperation strategies, as well as parets, this collaboration can be through social media, or through the advice of the teacher. As well as character that is implanted in the form of a religious character, honest, and disciplined, because these characters can print student sho have noble character, who has a quality personality, have an awereness of discipline and likes to practice the sunnah of the prophet that is to have a balance of morals and knowledge.